THE EFFECT OF ENVIRONMENT ANDAUDITOR INDIVIDUAL FACTORS ON AUDITOR JUDGMENT - Dianwicaksih Arieftiara; Pujiono Pujiono (STIE Perbanas Surabaya, 2013)
This research examinesfactors influence auditors, when they make ortake judgments duringaudit clients financial statement. Those factors were divided into two groups; environmentalfactors and auditor individual factors. Environmental factors are consists of internal auditorquality and communication between auditor and client. Whereas individual factors consist ofauditors experience and auditors attitude under time pressure. Furthermore,this research usedempires data are 86 respondents. The characteristic of those respondents were auditors whowork in public accounting firms on Surabaya, had experience three years minimum, ever auditclient who had internal audit departmentand ever audit the same client morethan once. The results of researches analysis could be learned that there are many factors influencing auditorjudgment. In conclusion, this study found that internal auditor quality, auditors experience andauditors attitude under time pressure has influence toward auditor judgment. Whereas, communication between auditor and client doesnt have influence toward auditor judgment.